2010
DOI: 10.1007/s00455-010-9301-5
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Input Pathways and Mechanisms in Swallowing: A Review

Abstract: Over the past 20 years, research on the physiology of swallowing has confirmed that the oropharyngeal swallowing process can be modulated, both volitionally and in response to different sensory stimuli. In this review we identify what is known regarding the sensory pathways and mechanisms that are now thought to influence swallowing motor control and evoke its response. By synthesizing the current state of research evidence and knowledge, we identify continuing gaps in our knowledge of these mechanisms and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
201
0
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(219 citation statements)
references
References 149 publications
5
201
0
13
Order By: Relevance
“…In humans, both regions have been implicated in swallowing and tongue movement (47), and, in primates, stimulation of the two regions has been shown to induce swallowing (48), along with tongue (49) and jaw (50) movements associated with mastication. These movements contribute to the oral preparatory phase of swallowing responsible for transporting liquid to the pharynx, where the sensory properties of the liquid can subsequently trigger initiation of swallowing (51). The increased BOLD signal in the two regions may thus represent an increase in the difficulty of manipulating the liquid to a position where swallowing can be instigated during the oral preparatory phase of swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, both regions have been implicated in swallowing and tongue movement (47), and, in primates, stimulation of the two regions has been shown to induce swallowing (48), along with tongue (49) and jaw (50) movements associated with mastication. These movements contribute to the oral preparatory phase of swallowing responsible for transporting liquid to the pharynx, where the sensory properties of the liquid can subsequently trigger initiation of swallowing (51). The increased BOLD signal in the two regions may thus represent an increase in the difficulty of manipulating the liquid to a position where swallowing can be instigated during the oral preparatory phase of swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the pharyngo-esophageal phases seem less likely to require, or be affected by, cognitive influences due to their non-volitionally controlled nature. 10,27 The relationship between motor dysfunction and swallowing functions is also not well defined. Indeed, the question of whether disease stage or severity is an indicator of dysphagia is a controversy in the field.…”
Section: Discussionmentioning
confidence: 99%
“…10 The pharyngo-esophageal swallowing sequence occurs via a brainstemdriven basic reflex, which utilizes sensory input from the oropharynx and esophagus. Because PD-related dysphagia is attributed to brainstem pathology, 11 research about swallowing dysfunction has focused mainly on the functions of brainstem swallowing centers, including the dorsal motor nucleus of the glossopharyngeus, the vagus nerves, and the nucleus of the solitary tract.…”
mentioning
confidence: 99%
“…João Rafael Sauzem Machado (1) , Eduardo Matias dos Santos Steidl (1) , Diego Fernando Dorneles Bilheri (1) , Mateus Trindade (2) , Guilherme Lopes Weis (2) , Paulo Roberto Oliveira de Jesus (3) , Marisa Bastos Pereira (4) , Renata Mancopes (5) (1) Universidade Federal de Santa Maria, RS -Brasil. 2) Serviço de Radiologia do Hospital Universitário de Santa Maria, RS -Brasil.…”
Section: Efeitos Do Exercício Muscular Respiratório Na Biomecânica Daunclassified
“…Steele et al 4 presented correlations between vertical and horizontal movement of this complex during swallowing and the predictive value for biomechanical of swallowing disorders. In this context, Troche et al 5 carried out a study in which they demonstrated the importance of respiratory muscle training, through the use of expiratory spirometry for the dysphagia rehabilitation in Parkinson patients.…”
Section: Introductionmentioning
confidence: 99%